2005
DOI: 10.1039/b507886e
|View full text |Cite
|
Sign up to set email alerts
|

Improved multi-elemental analyses by inductively coupled plasma-sector field mass spectrometry through methane addition to the plasma

Abstract: Changes in the analytical performance of double focusing sector field inductively coupled plasma mass spectrometry (ICP-SFMS) caused by addition of methane to the argon gas ICP were studied for approximately 100 isotopes of 70 elements. The parameters under consideration included instrumental background, analyte sensitivity, precision and formation of spectral interferences as functions of methane flow added to the sample gas. It was shown that for many analytes the capabilities of ICP-SFMS significantly impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 20 publications
6
106
2
Order By: Relevance
“…This may arise because of an increase in ionization efficiency for a number of elements, possibly due to charge transfer by an elevated level of C + species in the plasma, 20 and also as a consequence of differing aerosol properties (i.e., surface tension and density) that increase the nebulization efficiency compared to solutions containing nitric acid. 1,21 LOQs are improved in the formic acid medium due to enhanced sensitivity, lower blank values and improved measurement precision.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may arise because of an increase in ionization efficiency for a number of elements, possibly due to charge transfer by an elevated level of C + species in the plasma, 20 and also as a consequence of differing aerosol properties (i.e., surface tension and density) that increase the nebulization efficiency compared to solutions containing nitric acid. 1,21 LOQs are improved in the formic acid medium due to enhanced sensitivity, lower blank values and improved measurement precision.…”
Section: Resultsmentioning
confidence: 99%
“…20 No results are presented for Cr in a formic acid medium as significant interference on even 53 Cr remains due to the presence of large concentrations of carbon arising from both the formic acid and constituents of the sample matrix. 22 As such, determination of Cr was only possible for samples subjected to the more complete oxidation achieved with microwave-assisted acid decomposition.…”
Section: Brazil Nut Samplesmentioning
confidence: 99%
“…Hence, the multi-elemental capabilities of ICP-SFMS are not compromised by methane addition and the method is applied for routine applications. 97,67 ICP-SFMS has been used at R ¼ 3000 to resolve spectral interferences caused by N 2 + and CO + on 28 Si + , and NOH + and NO + on 31 P + , thereby facilitating the speciation of these elements. As an example, polydimethylsiloxanes and their silanol breakdown products were investigated by size exclusion and reverse phase chromatography (RP-HPLC) using high mass resolution ICP-SFMS as element-specific detector for Si.…”
Section: Biological and Environmental Samplesmentioning
confidence: 99%
“…16 Rodushkin et al, 17 have also reported that the addition of methane to the spray chamber increased the signal intensity of some elements including Au. 17 In addition, the 200 presence of the organic solvent reduces the surface tension of the Au solution, which may improve nebulisation efficiency.…”
mentioning
confidence: 96%